Climate resilience in Jordan’s Jerash camp: integrating government plans, humanitarian action and climate investment - Al-Zu’bi, Maha; Ruckstuhl, Sandra; Leh, Mansoor; Khalifa, Muhammad; Akpoti, Komlavi; Umer, Yakob (International Water Management Institute, 2025)
This policy brief examines climate risks and resilience pathways in Jordan’s Jerash Camp—one of the country’s most densely populated Palestinian refugee settlements. Hosting 14% of the governorate’s population on just 0.055% of its land, the camp faces the three interconnected climate hazards of water scarcity, flash flooding, extreme heat, together with chronic infrastructure deficits. The study uses mixed-methods research combined with climate risk mapping, geospatial analysis, interviews, and field observations, to show how climate hazards intersect with socio-economic vulnerability and fragmented governance structures.